Effect of Wu Zhi San supplementation in LPS-induced intestinal inflammation and barrier damage in broilers - Sun, Han; Zheng, Xirui; Yang, Bowen; Yan, Mingen; Wang, Huiting; Yang, Shijing; Shi, Dayou; Guo, Shining; Liu, Cui (Frontiers in Veterinary Science, 2023)
Intestinal inflammation and barrier damage can inhibit the absorption and transportation of nutrients in the small intestine, and lead to various chronic diseases. Wu Zhi San (WZS) is a traditional Chinese formula composed of Schisandrae, Anemarrhenae, Lonicerae, and Glycyrrhizae that was made to cure intestinal inflammation and barrier damage in broilers. To evaluate the protective effect of WZS on intestinal inflammation and barrier damage of broilers under lipopolysaccharide (LPS) stress, a total of 200 one-day-old broilers were randomly divided into five groups, namely, the CON group, LPS group, and three WZS groups (WZS-H, WZS-M, and WZS-L). The groups were designed for stress phase I (days 15, 17, 19, and 21) and stress phase II (days 29, 31, 33, and 35). The protective effect of WZS on the intestinal tract was evaluated by measuring the levels of serum myeloperoxidase (MPO), diamine oxidase (DAO), super oxide dismutase (SOD), and serum D-lactate (D-LA) and the expression of inflammatory factors in jejunum. The results showed that the diet supplemented with WZS could significantly reduce serum MPO, DAO, and D-LA levels and jejunal CD in broilers (p < 0.05), increase serum SOD levels and jejunal VH (p < 0.05), significantly downregulate the expression of NF-κB, TLR4, MyD88, and inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-10), and upregulate Claudin-1, Occludin-1, and ZO-1 in broiler jejunum mucosa (p < 0.05). On the other hand, WZS could significantly reduce the protein expression of NF-κB (p65) in broiler jejunum (p < 0.05). These results indicate that supplementing WZS in the diet can reduce intestinal inflammation and alleviate intestinal barrier damage, and by inhibiting the NF-κB/TLR4/MyD88 signaling pathway, supplementation with WZS intervenes in LPS-induced stress injury in broilers.